FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KANTOR AKUNTAN PUBLIK SECARA SUKARELA - Lumbantobing, Yuvita Chantri; Sudarno, Sudarno (Diponegoro Journal of Accounting, 2015)
The reseacrh aims to knows empirical evidence all factors influencing auditor switching on company sector non finance listed in Indonesia Stock Exchange in 2008-2013 period. The determinant factors are analysized using many proxy such as CEO turnover (CEO), audit opinion (OPINI), clients size (LnTA), financial distress (DER) and company growth(∆S). The population of this research is company sector non finance which is listed in “Bursa Efek Indonesia” (BEI) during period 2008-2013. Sampling is conducted based on method which used in this research is method purposive sampling, that based in criteria has been determined research hypothesis are tested by logistic regression analytical method. Result indicates that variables which have significantly effect to the voluntary auditor switching is only client size. Variables like CEO turnover, audit opinion, financial distress and company growth have no significant effect to voluntary auditor switching.